Theoretical Perspectives of Police Science and Their Implementation in Police Duties - Tagor Hutapea; Alexander Evan; Rahmadsyah Lubis (Indonesian Journal of Social Development, 2026)
This study aims to formulate a conceptual understanding of police science and analyse its implementation in policing practices by synthesising global policing literature. The research adopts a qualitative conceptual approach using a systematic literature review of academic publications, including classical and contemporary studies related to policing theories, strategies, and institutional development. The analysis focuses on major policing approaches such as community policing, problem-oriented policing, intelligence-led policing, and evidence-based policing to identify theoretical patterns, developments, and research gaps. The findings indicate that police science is an interdisciplinary field that integrates criminology, sociology, law, and public policy to explain policing institutions, strategies, and practices. The study also finds that the development of police science has shifted towards evidence-based approaches, emphasising the integration of empirical research, professional judgement, and community values in policing decisions. However, most existing studies still concentrate on operational policing strategies rather than positioning police science as a comprehensive academic discipline with a clear theoretical foundation. This study proposes a conceptual definition of police science as an applied interdisciplinary discipline and develops a theoretical framework linking police science, policing strategies, operational practices, and public legitimacy. The findings contribute to strengthening the conceptual foundation of police science and provide direction for integrating scientific knowledge into policing practices.